Design of helical groove/hollow nanofibers via tri-fluid electrospinning. (July 2021) - Zhao, Tienan; Zheng, Yuansheng; Zhang, Xiaomin; Teng, Defang; Xu, Yuanqiang; Zeng, Yongchun
Graphical abstract: In tri-fluid electrospinning, combined with appropriate polymers and spinneret structure, we design and successfully prepared a new type of multilevel structured nanofibers with helical groove/hollow structures. And the resultant fiber membranes exhibit improved functions. Highlights: The multi-component nanofiber membrane with helical groove/hollow structure is designed and successfully fabricated. A new designed tri-fluid electrospinning system for producing multilevel structured nanofibers. The complex mechanism of fiber morphology formation is explored. The resultant membrane with complex structure exhibit advantages in wettability and mechanical behavior. Abstract: Electrospinning of multilevel structured micro/nanofibers have obtained considerable attention recently. In this study, inspired by the unique properties and functions of helical, groove and hollow structures in nature, we prepared a new type of multilevel structured nanofibers with helical and groove/hollow structures. Based on the fiber formation mechanism, a combination of cellulose acetate and other appropriate polymers were applied to generate helical groove/hollow nanofibers using a designed tri-fluid electrospinning system. By varying the capillary dispositions of the spinneret, the fibers with helical groove and helical hollow structures were obtained. To explore the forming process of the composite fibers, high speed photography was employed to record the Taylor cone and jet path under the spinnerets. By characterizing the morphologies and specific functions of the as-prepared nanofibers, the unique helical groove/hollow structure were generated and present good properties in wettability and mechanical behavior.